Holistic Learning Strategies in Early Childhood Education: Developing Children's Emotional Intelligence and Creativity - Laila Nursafitri (Pt. Anagata Sembagi Education, 2025)
Holistic learning has gained increasing prominence in early childhood education due to its capacity to integrate emotional, social, sensory, and cognitive experiences into meaningful developmental pathways. This study investigates how holistic learning strategies foster emotional intelligence and creativity in young children through a systematic literature review of 35 peer reviewed studies published in the last decade. The findings indicate that arts-based learning, nature-based experiential learning, digital and interactive mediation, and social-cooperative learning consistently strengthen emotional awareness, empathy, self-regulation, curiosity, imagination, and divergent thinking. Sustainability, however, requires strong curriculum policy alignment, teacher readiness, parental collaboration, cultural value support, and leadership commitment to holistic pedagogy. This study contributes by synthesizing a conceptual framework that identifies the core components and institutional supports necessary for holistic programs to effectively develop emotional intelligence and creativity in early childhood